The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4103/sjmms.sjmms_630_20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fear of COVID-19 on Mental Well-Being and Quality of Life among Saudi Adults: A Path Analysis

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has been very disruptive, and thus is likely to result in substantial challenges to mental health. Objectives: This study aimed to investigate the effects of fear of COVID-19 on the mental well-being and quality of life among Saudi adult population and to evaluate the impact of perceived social support. Materials and Methods: This cross-sectional study used an anonymous online surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 48 publications
7
40
0
Order By: Relevance
“…In this cross-sectional correlational study of 1,030 immunocompromised and chronic disease patients, the majority of participants experienced a certain level of fear of acquiring the infection, 21.44% were identified as anxiety cases, and 19.4% were considered borderline anxiety cases during the outbreak of COVID-19 in SA. Also, it is clear that the participants show considerable levels of fear and health anxiety as a group, and the levels reported in this study are above the cut-off points identified for each of these variables in the previous studies (using the same scales; FCV-19S and HADS-A) in healthy adult populations [ 28 , 29 ]. In general, women and older patients with chronic diseases who were receiving immunosuppressants were more likely to have high levels of fear and health anxiety.…”
Section: Discussionsupporting
confidence: 61%
“…In this cross-sectional correlational study of 1,030 immunocompromised and chronic disease patients, the majority of participants experienced a certain level of fear of acquiring the infection, 21.44% were identified as anxiety cases, and 19.4% were considered borderline anxiety cases during the outbreak of COVID-19 in SA. Also, it is clear that the participants show considerable levels of fear and health anxiety as a group, and the levels reported in this study are above the cut-off points identified for each of these variables in the previous studies (using the same scales; FCV-19S and HADS-A) in healthy adult populations [ 28 , 29 ]. In general, women and older patients with chronic diseases who were receiving immunosuppressants were more likely to have high levels of fear and health anxiety.…”
Section: Discussionsupporting
confidence: 61%
“…More than half of the respondents reported some impairment of social activities, and many of them reported “severely impaired” leisure activities; this could be attributed in part to the panic of being in contact with the “probably” infected persons in overcrowded places, and, on the other hand, to the lockdown that was imposed by the health and political authorities for more than 3 months. These findings are consistent with what was reported in some other studies [ 5 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The sample size was determined by using the G-power software. According to the results of a study performed by Alyami et al, (2021) on the fear of COVID-19 and with considering standard deviation (SD)= 5.67, d (percision)= 0.07 around the mean (m= 16.73), effect size d= 0.21, α=0.05, and power= 95%, the sample size was calculated 248 persons; in J o u r n a l P r e -p r o o f Journal Pre-proof this study 250 participants were investigated.…”
Section: Type Of Study and Participantsmentioning
confidence: 99%